Financial Knowledge, Financial Attitude, and Personality as Antecedents of Financial Management Behavior - Mustika Rahmi; Fahd Al-Shaghdari; Tina Sulistiyani; Fanji Amwa (Universitas Ahmad Dahlan, 2023)
Purpose: This study looks into the relationship between financial management behavior and financial knowledge, attitude, and personality. Design/Methodology/Approach- The study population included Yogyakarta's Micro, Small, and Medium-Sized Ceramic Crafts Enterprises. Data for this study was collected through purposeful sampling, with 45 respondents forming up the study sample. Analysis processes were performed on this research data using an analysis program called SPSS. Findings-The findings show that personality, financial attitude, and financial knowledge positively influence the financial management behavior of Yogyakarta's Micro, Small, and Medium-Sized Ceramic Crafts Enterprises. Research limitations/implications- To promote the growth of financial management behavior, the ceramic craft industry must maximize its financial knowledge, attitude, and personality. Originality/value-The study of financial management behavior in Micro, Small, and Medium Enterprises, especially ceramic crafts, is still quite limited. In addition, no previous research has discussed financial management behavior by adding personality variables as one of the influencing factors.